Karinding: Dari Ungkapan Hati Menjadi Karya Seni (Sebuah Tinjauan Etnomusikologi) - Zulfikar Alamsyah; Agus Suherman (Universitas Negeri Surabaya, 2022)
Karinding is a traditional West Javanese musical instrument made of bamboo. Now the existence of these traditional musical instruments has started to bloom again being preserved by young people. By using a descriptive analytic method through an ethnomusicological approach, literature study techniques, and observation, this study aims to describe aspects of function, musical, instruments, and support. The results of this study include four things. First, in the aspect of Karinding function experienced significant changes. Starting from a communication tool until now it has changed its function as a medium of entertainment, education, and commodities. Second, in terms of musical Karinding is experiencing development, Karinding buhun, which at first only could imitate the sound and rhythm of insects and tools around the community, has developed with the type of Karinding toél which has diatonic and pentatonic scales. Third, this Karinding musical instrument is divided into three parts namely pancepengan, cécét ucing, and paneunggeul. These three parts of Karinding have their own philosophical values ​​which are closely related to the beliefs of the Sundanese people. Fourth, the Karinding Attack community and the Karinding Group in Cirama Girang Village have become one of the activist communities in preserving the traditional arts of Karinding in West Java. From this study it can be concluded that Karinding is a musical instrument that was born from folklore which has a life learning philosophy to become a patient, confident and simple human being. This musical instrument has undergone revitalization to become a traditional musical performance. In addition, the Karinding art, which was declared almost extinct, has now been revived and is in great demand, especially by young people.